Safety and efficacy of intralesional steroid injection for aggressive fibromatosis - Dumnoensun Pruksakorn (2018)
© 2017 The Author(s). Background: Treatment of recurrent aggressive fibromatosis (AF) following surgical resection is a clinical challenge. Non-steroidal anti-inflammatory drugs (NSAIDs) have been reported to be an effective option for controlling the disease. However, long-term NSAID use can result in unfavorable complications. This study was a trial of the use of intralesional steroid injection (ILSI) including investigation of safety margins and clinical outcomes of high-dose steroids for local use treatment of AF. Methods: A prospective cohort study was conducted to evaluate the safety and efficacy of particulate corticosteroids for AF. Intralesional steroid injections of Kanolone® guided by ultrasound were given monthly for three consecutive months with 1 mg/kg/episode (a total of 3 mg/kg). Patients were followed up monthly for 3 months at the time of each monthly injection and then for an additional 3 months after the last injection. Complications from the procedure and clinical outcomes were monitored. Results: Eight recurrent AF patients completed the full 6-month evaluation process. No procedure-related complications were reported either during the injection period or the follow-up period. None of the patients developed Cushingoid features. The highest number of complication events, all of which were mild or detectable only by laboratory analysis, occurred during the month following the second injection. Triamcinolone levels were significantly increased 24 h after injection, and four of the eight cases developed hypothalamic-pituitary-axis suppression. Tumors were stabilized in 83.3% of the cases during the study period, and pain and functional ability scores improved significantly. Conclusions: Intralesional steroid injection appears to be a safe and effective alternative treatment for recurrent AF. Trial registration:TCTR20150409001 ; Registered date: 9 April 2015; The safety and result of intratumoral steroid injection for aggressive fibromatosis.